2013
DOI: 10.1111/age.12025
|View full text |Cite
|
Sign up to set email alerts
|

Two completely linked polymorphisms in thePPARGtranscriptional regulatory region significantly affect gene expression and intramuscular fat deposition in the longissimus dorsi muscle of Erhualian pigs

Abstract: This article is the first to report the significant effect of PPARG promoter polymorphisms on the expression and intramuscular fat (IMF) content in the longissimus dorsi (LD) muscle of Erhualian pigs. Polymorphic sites for the PPARG upstream transcriptional regulatory region were scanned by direct sequencing of two DNA pools consisting of individuals with significantly different IMF content (P < 0.05). Two SNPs (c.-1633C>T and c.-1572G>A) were identified, with different allele distribution between these two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…PPARγ is involved in the adipocyte differentiation and improved IMF deposition and adipogenesis in muscle fibers which determines IMF content (Wang et al, 2013). In the present experiment, the PPARγ expression in muscle tissues of Jinhua and Landrace pigs was significantly and positively correlated with IMF content.…”
Section: The Relationship Between Gene Expression and Carcass Lean Imf Contentsupporting
confidence: 47%
“…PPARγ is involved in the adipocyte differentiation and improved IMF deposition and adipogenesis in muscle fibers which determines IMF content (Wang et al, 2013). In the present experiment, the PPARγ expression in muscle tissues of Jinhua and Landrace pigs was significantly and positively correlated with IMF content.…”
Section: The Relationship Between Gene Expression and Carcass Lean Imf Contentsupporting
confidence: 47%
“…PPARG regulates lipid metabolism and glucose homeostasis and promotes adipocyte differentiation and fat deposition (Vanden Heuvel and Peters, 2010). Previous studies have found that the polymorphisms of PPARG could significantly affect gene expression and intramuscular fat deposition in pigs (Wang et al, 2013). In addition, PPARG could enhance PLIN1 expression by DNA demethylation on PPAR-response elements of PLIN1 gene promoter upon differentiation (Fujiki et al, 2013).…”
Section: Detection Of Candidate Genes That Affect Imf Contentmentioning
confidence: 99%
“…141 Furthermore, the polymorphism in the PPARg (TA haplotype favorable over CG haplotype) upstream transcriptional regulatory region has been associated with higher IM. 174 On the contrary, a few other GWA have had limited success in the identification of the genetic drivers of IM percentage which could be due to variations including treatments, genetics etc., resulting in the similar phenotype. 175,176 High throughput genomic technologies using powerful SNP panels will have to be combined with phenomics approach to further understand the complexities of IM.…”
Section: Genetic Variations/qtl and Epigenetic Changes Associated Witmentioning
confidence: 99%